Influence of the surface roughness and oxide surface layer onto Si optical constants measured by the ellipsometry technique - Rozouvan, T.S.; Poperenko, L.V.; Shaykevich, I.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Si crystal surface after chemical etching was studied using ellipsometry, atomic force microscopy and scanning tunneling microscopy. The ellipsometric parameters as functions of light incidence angles at two light wavelengths 546.1 and 296.7 nm were measured. The calculations based on equations for the plane surface have shown that the refractive index and absorption coefficient values are different from those determined earlier. Two models for surface layers were developed. After etching, the upper layer contains chemical compounds and the lower layer characterizes the sample roughness. By applying Airy’s formula to ellipsometric data, optical constants and thicknesses of the layers were obtained. The calculated values of bulk Si optical constants wholly correspond to the data from literature. The calculated thickness of the lower layer is similar to that obtained through scanning tunneling microscopy measurements. Calculations based on Maxwell-Garnett and Bruggeman equations were performed to determine the content of silicon particles within the lower rough layer.